2008
DOI: 10.1016/j.resuscitation.2007.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Soluble epoxide hydrolase gene deletion reduces survival after cardiac arrest and cardiopulmonary resuscitation

Abstract: Summary-The P450 eicosanoids epoxyeicosatrienoic acids (EETs) are produced by cytochrome P450 arachidonic acid epoxygenases and metabolized through multiple pathways, including soluble epoxide hydrolase (sEH). Pharmacological inhibition and gene deletion of sEH protect against ischemia/reperfusion injury in brain and heart, and against hypertension-related end-organ damage in kidney. We tested the hypothesis that sEH gene deletion improves survival, recovery of renal function and pathologic ischemic renal dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 25 publications
1
48
1
1
Order By: Relevance
“…However, in cardiac arrest (CA) and the resuscitation mouse model, the survival rate of sEH knockout mice model was significantly lower than wild-type, and reduced sEH levels or function reduce survival from cardiac arrest. This result is contrary to the previous hypothesis that sEH gene deletion improves survival and protect against ischemia/reperfusion injury [36]. To find subcellular location and genetic polymorphisms of sEH, sEH cDNA was cloned into vectors and transfected into different cell lines.…”
Section: Introductioncontrasting
confidence: 65%
See 1 more Smart Citation
“…However, in cardiac arrest (CA) and the resuscitation mouse model, the survival rate of sEH knockout mice model was significantly lower than wild-type, and reduced sEH levels or function reduce survival from cardiac arrest. This result is contrary to the previous hypothesis that sEH gene deletion improves survival and protect against ischemia/reperfusion injury [36]. To find subcellular location and genetic polymorphisms of sEH, sEH cDNA was cloned into vectors and transfected into different cell lines.…”
Section: Introductioncontrasting
confidence: 65%
“…In the acute systemic inflammation model, the sEH-null mice show a survival advantage over normal control [35]. In sEH-null mice, plasma levels of epoxy fatty acids were increased, fatty acid diols levels were decreased, and renal formation of epoxyeicosatrienoic and dihydroxyeicosatrienoic acids was markedly lower for versus wild-type mice [36,37]. However, in cardiac arrest (CA) and the resuscitation mouse model, the survival rate of sEH knockout mice model was significantly lower than wild-type, and reduced sEH levels or function reduce survival from cardiac arrest.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Gross et al (5) reported no differences in heart rate and blood pressure at 30 min of occlusion and 2 h of reperfusion in a rat model of regional myocardial I/R in between groups tested with a similar dose of 14,15-EET. In contrast to regional myocardial ischemia, where sEHKO mice are protected, in cardiac arrest-induced whole body ischemia, sEHKO mice were at a disadvantage, presumably due to excessive vasodilation and an inability to maintain blood pressure after cardiopulmonary resuscitation (6).…”
Section: Discussionmentioning
confidence: 96%
“…CA/CPR is an established model of renal ischemia-reperfusion injury (7,17,18,20). Although the most extensive in vivo findings about renal ischemia have been derived from focal renal pedicle occlusion models, most human AKI occurs after whole body ischemia-reperfusion (25,46).…”
Section: Discussionmentioning
confidence: 99%
“…We performed normothermic CA/CPR as previously described (17,18,20). Briefly, after weighing, general anesthesia was induced with 4% isoflurane in Table 1.…”
Section: Methodsmentioning
confidence: 99%